The effect of electromagnetic waves on the human body (Eurasian Research Bulletin, 2023)
Artificial electromagnetic waves are the most common and rapidly growing source of exposure in the modern world, including exposure to several groups of frequencies: extremely low frequencies from power lines, car hybrid batteries, and high-voltage lines (>3 Hz-3 kHz); radio frequencies; microwave frequencies, including millimeter waves (3 kHz-300 GHz) from cell phones towers, base stations, and wireless devices, and intermediate frequencies, so-called "dirty electricity" generated by power cables